2017
DOI: 10.1128/mcb.00418-17
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR-Bach2 Cascade Controls Cell Cycle and Class Switch Recombination during B Cell Differentiation

Abstract: The transcription factor Bach2 regulates both acquired and innate immunity at multiple steps, including antibody class switching and regulatory T cell development in activated B and T cells, respectively. However, little is known about the molecular mechanisms of Bach2 regulation in response to signaling of cytokines and antigen. We show here that mammalian target of rapamycin (mTOR) controls Bach2 along B cell differentiation with two distinct mechanisms in pre-B cells. First, mTOR complex 1 (mTORC1) inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…PI3K is likely to participate in this process. Prolonged PI3K activity decreases BACH2 through at least two different mechanisms: (a) at the protein level, through AKT‐mTORC1–mediated phosphorylation of BACH2, leading to cytoplasmic localization and degradation; (b) at the mRNA level, through inhibition of FOXO1 which promotes Bach2 transcription . BACH2 also blocks Prdm1 expression and therefore PC differentiation (Figures and ).…”
Section: Pi3k In Plasma Cell and Memory B‐cell Formationmentioning
confidence: 97%
“…PI3K is likely to participate in this process. Prolonged PI3K activity decreases BACH2 through at least two different mechanisms: (a) at the protein level, through AKT‐mTORC1–mediated phosphorylation of BACH2, leading to cytoplasmic localization and degradation; (b) at the mRNA level, through inhibition of FOXO1 which promotes Bach2 transcription . BACH2 also blocks Prdm1 expression and therefore PC differentiation (Figures and ).…”
Section: Pi3k In Plasma Cell and Memory B‐cell Formationmentioning
confidence: 97%
“…In the absence of Bach2, AP-1/IRF4 complex binding is increased, leading to enhanced transcriptional activity in response to TCR signals. Interestingly, the TCR-induced kinase AKT has been identified to inactivate Bach2 by mediating its phosphorylation at Serine-535 [49][50][51] . This provides a feedback mechanism by which the magnitude of the transcriptional response to TCR signals may be further modulated by Bach2.…”
Section: Bach2 Is Required For Of Treg Cell Expansion and Maintenancementioning
confidence: 99%
“…4) (Dowling et al, 2010;Fingar et al, 2004). A recent study has also demonstrated that mTOR regulates B-cell proliferation by controlling the transcription and translation of the BACH2 transcription factor, which targets cyclin D3 to initiate the cell cycle (Tamahara et al, 2017). In plants, TOR is highly expressed in rapidly growing tissues such as the embryo, shoot meristem, root meristem and lateral root primordia, implicating the involvement of TOR signaling in cell proliferation (Menand et al, 2002).…”
Section: Downstream Targets Of Torc1mentioning
confidence: 99%